Diseño y construcción de un sistema de reparto de alimentos para pollos de postura en la avícola “elycar”, ubicada en el barrio tandalivi Latacunga. - Borja Vargas, Francisco Nicolas (2019)
The present project was carried out in the TANDALIVI Sector, Jose Guango Bajo road, Aláquez Neighborhood, Latacunga, in order to carry out and verify the design and construction of an automatic food distribution system for in the "ELYCAR" poultry into a chicken shed; to reduce the time spent in the manual distribution of food for birds, through research and experimental tests will be applied for production, with technological methods that help to optimize time through a structural design, which allows the researchers to automatically supply the food by its hoppers which can support the load to along the feeders. Currently, terms such as automatic control, and automated feeding systems can be applied in different types of feeding systems for birds, in a more controlled environment; in addition, the system can be the most effective method to reduce efforts, due to the introduction of a gear motor and a power transmission system that will replace human work, guaranteeing the birds feeding, in shorter times, returning profits and investment in the medium term. So, it is possible to control the feeding, with the implementation of this system, at any desired time through an easily manipulated control board.